2005
DOI: 10.1111/j.1365-3040.2005.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leaf structure and photosynthetic characteristics of C3 and C4Alloteropsis semialata subspecies

Abstract: Alloteropsis semialata (R. Br.) Hitchcock includes both C 3 and C 4 subspecies: the C 3 subspecies eckloniana and the C 4 subspecies semialata . We examined the leaf structural and photosynthetic characteristics of these plants. A. semialata ssp. semialata showed high activities of photosynthetic enzymes involved in phosphoenolpyruvate carboxykinasetype C 4 photosynthesis and an anomalous Kranz anatomy. Phosphoenolpyruvate carboxylase; pyruvate, Pi dikinase and glycine decarboxylase (GDC) were compartmentalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 51 publications
8
69
0
Order By: Relevance
“…S1), which implies some Rubisco activity in these cells, confirming previous reports (Ueno and Sentoku 2006; Lundgren et al. 2016).…”
Section: Resultssupporting
confidence: 91%
“…S1), which implies some Rubisco activity in these cells, confirming previous reports (Ueno and Sentoku 2006; Lundgren et al. 2016).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, special care was taken to include the appropriate components in the extraction medium to maximise the extraction and recovery of the enzyme activities. The methods adopted in the present study were similar to those recently reported by other authors (Bailey et al 2007;Marshall et al 2007;Sudderth et al 2007), and the values obtained for the activities of the three C 4 acid decarboxylases are in the same range as previously reported for grass species (Gutierrez et al 1974;Hatch et al 1975Hatch et al , 1982Prendergast et al 1987;Ueno and Sentoku 2006).…”
Section: Effects Of Leaf Dehydration On Enzyme Activitiesmentioning
confidence: 72%
“…Br.) Hitchcock (Ueno and Sentoku, 2006), bridge the genetic gap between C 3 and C 4 species. Currently, attempts have been made to genetically manipulate photosynthesis by introducing the genes for C 4 photosynthetic enzymes into C 3 plants (reviewed in Surridge, 2002).…”
Section: Genetic Control Of Photosynthetic Metabolismmentioning
confidence: 99%